circRNA_0001679/miR-338-3p/DUSP16 axis aggravates acute lung injury - Zhu Jiang; Zhong Fukuan; Chen Futao; Yang Yang; Liao Yingying; Cao Lifeng; Zhou Yong; Bai Qiaohong (Open Medicine, 2022)
Acute lung injury (ALI) is a respiratory disorder characterized by acute respiratory failure. circRNA mus musculus (mmu)-circ_0001679 was reported overexpressed in septic mouse models of ALI. Here the function of circ_0001679 in sepsis-induced ALI was investigated. In vitro models and animal models with ALI were, respectively, established in mouse lung epithelial (MLE)-12 cells and C57BL/6 mice. Pulmonary specimens were harvested for examination of the pathological changes. The pulmonary permeability was examined by wet-dry weight (W/D) ratio and lung permeability index. The levels of tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-1β in the bronchoalveolar lavage fluid (BALF), the lung tissues, and the supernatant of MLE-12 cells were measured by enzyme linked immunosorbent assay . Apoptosis was determined by flow cytometry. Bioinformatics analysis and luciferase reporter assay were used to assess the interactions between genes. We found that circ_0001679 was overexpressed in lipopolysaccharide (LPS)-stimulated MLE-12 cells. circ_0001679 knockdown suppressed apoptosis and proinflammatory cytokine production induced by LPS. Moreover, circ_0001679 bound to mmu-miR-338-3p and miR-338-3p targeted dual-specificity phosphatases 16 (DUSP16). DUSP16 overexpression reversed the effect of circ_0001679 knockdown in LPS-stimulated MLE-12 cells. Furthermore, circ_0001679 knockdown attenuated lung pathological changes, reduced pulmonary microvascular permeability, and suppressed inflammation in ALI mice. Overall, circ_0001679 knockdown inhibits sepsis-induced ALI progression through the miR-338-3p/DUSP16 axis.